Synthesis, antimalarial activity, and molecular dynamic approaches of salophen metal complexes - Ali, Amatul Hamizah; Mukhtar, Nur Hafizah; Ling, Ng Yee; Norazmi, Nur Aqilah Zahirah; Agustar, Hani Kartini; Ling, Lau Yee; Abd Karim, Nurul Huda; Yusoff, Siti Fairus Mohd; Borzehandani, Mostafa Yousefzadeh; Hassan, Nurul Izzaty (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaria is still one of the main infectious diseases in tropical climates. Various antimalarial drugs have been introduced before, such as chloroquine, primaquine, and artemisinin. However, the effectiveness of antimalarial drugs is complicated by the spread of Plasmodium parasites’s resistance. This study was carried out to explore metal complexes based on Schiff base ligands with good potential as antimalarial agents. Four salophen-based ligands a-d, and eight salophen metal complexes 1a-4a and 1b-4b were synthesized via Schiff base condensation reaction. Antimalarial properties of these compounds were investigated by plasmodium lactate dehydrogenase assay against P. falciparum 3D7, which showed that 1a, 3a, and 4b possessed active parasite inhibitory effect in vitro study (IC50: 14.74, 19.38, and 12.13 µM, respectively). Molecular docking analysis showed that compounds 1a, 3a, and 4b showed good binding affinity values, i.e. -9.7, -8.9, and -9.5 kcal/mol on PfDHFR-TS. Furthermore, the molecular simulations showed that 1a and 3a accommodated in the receptor’s pocket where some polar surfaces surrounded the compounds. However, 4b built the highest conformational stable receptor-ligand complex system when positioned in the receptor’s hydrophobic pocket. Thus, PfDHFR-TS is a specific parasite protein target for the salophen metal complex. In conclusion, this study found that the salophen metal complex has a high potential to be developed as an antimalarial agent and can be a template structure for forming antimalarial drugs to fight resistance cases.